CENDAWAN ENTOMOPATOGEN BEAUVERIA BASSIANA DALAM MENGENDALIKAN TELUR HAMA PENGGEREK UBI JALAR (CYLAS FORMICARIUS) - ARTANTI, DITA; Prayogo, Yusmani (LenteraBio: Berkala Ilmiah Biologi, 2013)
One obstacle in maintaining productivity and quality of sweet potato is Cylas formicarius pests (Coleoptera: Curculionidae). This study aimed to determine the effect of entomopathogenic fungi B. bassiana to control the eggs of C. formicarius. The method used was a Completely Randomized Design (CRD). The treatment was applied at various ages eggs that age 0 days, 1 day, 2 days, 3 days, 4 days, 5 days, 6 days, and 7 days. Each ages eggs sprayed using the fungi B. bassiana with a concentration of 108 conidia/ml with 3 repetitions. Observations were made every day for 7 days after application. Analysis of the data by one-way ANOVA and Duncan test level 5%. The results showed that B. bassiana effective in suppressing hatching eggs C. formicarius of 100% at the age of eggs 0 days to 4 days better than age of eggs 5 days to 7 days that have opportunity hatching eggs of 20-60%.